Lost in the mail: A field experiment on crime - Castillo, Marco; Petrie, Ragan; Torero, Máximo; Viceisza, Angelino (Wiley, 2014)
Stealing, shirking, and opportunistic behavior in general can create barriers to the development of markets. The costs associated with such behavior are shared by both firms and individuals and can be large enough to even prevent the initiation of trade. Measurement of these costs is difficult because information is not available for transactions that fail to occur. We use a field experiment to identify opportunistic crime in a task that is important and relevant for trade: the delivery of mail. We subtly manipulate the content and information available in mail sent to households across neighborhoods that vary by income, and detected high levels of shirking and stealing. Eighteen percent of the mail never arrived at its destination, and significantly more was lost if there was even a slight hint of something additional inside the envelope. Our results demonstrate the importance of transaction costs created by crime and that not all populations are equally affected. Middle‐income neighborhoods suffer the most. (JEL C93, K42, H41, L87, O21)